The role of the mTOR pathway in models of drug-induced reward and the behavioural constituents of addiction. (November 2020) - Ucha, Marcos; Roura-Martínez, David; Ambrosio, Emilio; Higuera-Matas, Alejandro
Background: Exposure to drugs of abuse induces neuroadaptations in critical nodes of the so-called reward systems that are thought to mediate the transition from controlled drug use to the compulsive drug-seeking that characterizes addictive disorders. These neural adaptations are likely to require protein synthesis, which is regulated, among others, by the mechanistic target of the rapamycin kinase (mTOR) signalling cascade. Methods: We have performed a narrative review of the literature available in PubMed about the involvement of the mTOR pathway in drug-reward and addiction-related phenomena. Aims: The aim of this study was to review the underlying architecture of this complex intracellular network and to discuss the alterations of its components that are evident after exposure to drugs of abuse. The aim was also to delineate the effects that manipulations of the mTOR network have on models of drug reward and on paradigms that recapitulate some of the psychological components of addiction. Results: There is evidence for the involvement of the mTOR pathway in the acute and rewarding effects of drugs of abuse, especially psychostimulants. However, the data regarding opiates are scarce. There is a need to use sophisticated animal models of addiction to ascertain the real role of the mTOR pathway in this pathology and not just in drug-mediated reward. The involvement of this pathway in behavioural addictions and impulsivity should also be studied in detail in the future. Conclusions: Although there is a plethora of data about the modulation of mTOR by drugs of abuse, the involvement of this signalling pathway in addictive disorders requires further research.